Spinal Meningioma Surgery through the Ages—Single-Center Experience over Three Decades - Hanah Hadice Gull; Mehdi Chihi; Oliver Gembruch; Tobias Schoemberg; Thiemo Florin Dinger; Klaus Peter Stein; Yahya Ahmadipour; I. Erol Sandalcioglu; Ulrich Sure; Neriman Özkan (Medicina, 2022)
Background and Objectives: Spinal meningiomas, which are well characterized and are most frequently intradural extramedullary tumors, represent 25% of all intradural spinal tumors. The goal of this study was to compare the outcomes of surgically treated patients with spinal meningiomas in two time intervals with special emphasis on postoperative functional outcomes. Methods: Patients with spinal meningiomas admitted to our department between 1990 and 2020 were enrolled and divided into a historic cohort (HC; treated 1990–2007) and a current cohort (CC; treated 2008–2020). Patients’ clinical data and surgical and radiological reports were retrospectively analyzed up to 5 years. Preoperative and postoperative neurological function were assessed using the modified McCormick Scale (mMCS). The Charlson Comorbidity Index (CCI) was used to evaluate the effect of comorbidities on the preoperative status and postoperative outcome. Results: We included 300 patients. Participants in the CC (n = 144) were significantly younger compared to those in the HC (n = 156), with twice as many patients <50 years of age (p < 0.001). The most common tumor location was the thoracic spine (n = 204). The median follow-up was 38.1 months (±30.3 standard deviation). A symptom duration until surgery <12 months was significantly associated with an earlier improvement in the mMCS (p = 0.045). In the CC, this duration was shorter and patients’ neurological function at the first and last follow-ups was significantly better than for those in the HC (p < 0.001 for both). Conclusions: Our study results suggested that the impact of surgical management and postoperative rehabilitation on spinal meningioma patients’ long-term neurological outcome has reached important milestones over the last decades. An earlier diagnosis led to earlier surgical treatment and improved patients’ postoperative neurological recovery. Our results exposed that surgical therapy for spinal meningioma should be performed within 12 months after appearance of symptoms to achieve a better recovery.